Implementation of the Independent Campus Learning Program in creating a place for creativity at SD 068004 Medan City - Amelia Putrisari; Fajar Utama Ritonga; Mujahid Widian Saragih (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
This research is entitled